Comprehensive Kinetics and Thermodynamics Analysis of Salix psammophila Biomass Pyrolysis Using Multicomponent Modeling - Tang, Maoyi; Yao, Zhitong; Wang, Haoqi; Li, Huanxuan; da Silva, Jean Constantino Gomes; Pejic, Ljiljana Medic; Manić, Nebojša; Sun, Yuhang; Kumar, Akash; Chen, Yang; Liu, Jie; Qi, Wei (ACS sustainable chemistry & engineering, 2025)
Multicomponent deconvolution enables precise peak separation and accurate determination of kinetic parameters and improves identification of the underlying mechanisms of biomass pyrolysis. In the present study, the multicomponent kinetics and thermodynamics of Salix psammophila pyrolysis were investigated to evaluate its bioenergy potential. Thermogravimetric analysis coupled with peak deconvolution revealed three stages involving four components (pseudoextractives/PS-EC, pseudohemicellulose/PS-CL, pseudocellulose/PS-CL, and pseudolignin/PS-LG) with the corresponding peak temperatures of 246.83–270.83, 291.59–315.59, 335.26–359.26, and 386.14–410.14 °C, respectively. Pyrolysis gas chromatography/mass spectrometry analysis indicated dominant products of acids, phenolics, and alkanes. Activation energies for each pseudocomponent from four isoconversional methods were comparable, following an order of PS-EC (134.96 kJ mol–1) < PS-HC (151.59 kJ mol–1) < PS-CL (166.93 kJ mol–1) < PS-LG (239.65 kJ mol–1). Master plot analysis suggested an order-based reaction mechanism. Positive enthalpy changes (127.83–227.33 kJ mol–1) and Gibbs free energy changes (144.73–193.03 kJ mol–1) indicated higher energy barriers, especially for PS-LG, and limited spontaneity of conversion. These findings highlighted the potential of S. psammophila as a viable feedstock and offered critical insights into reactor design and process optimization for industrial applications.